TANTANGAN GURU PAI MENGIMPLEMENTASIKAN KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Setiawan, Selamet Awan (Jurnal Inovasi Pendidikan Madrasah Ibtidaiyah (JIPMI), 2024)
This study aims to analyze the challenges faced by Islamic education teachers in implementing an independent curriculum for learning Islamic religious education. The independent curriculum, which emphasizes freedom of learning, creativity, and independence of learners, presents challenges for Islamic education teachers in maintaining a balance between Islamic values and the educational objectives promoted by this curriculum. This research uses the literature analysis method, collecting and analyzing relevant literature to identify common themes regarding these challenges. The results of the literature analysis show that Islamic education teachers face several challenges in implementing the independent curriculum. Firstly, the challenge of integrating Islamic values with the freedom to learn approach. Teachers need to develop learning strategies that allow learners to think critically and creatively, while still maintaining the essence of Islamic values. Secondly, the challenge of maintaining relevance between Islamic teachings and modernizing developments. Teachers need to show clear connections between Islamic teachings and learners contemporary needs. Thirdly, the challenge of utilizing technology and digital learning tools in accordance with Islamic values. The use of technology needs to be integrated wisely to remain consistent with religious principles. This study underlines the importance of building an inclusive and learner-centered approach to learning so that Islamic education teachers can face these challenges more effectively.